Lunar, Diurnal and Tidal Periodicity in Relation to the Prawn Abundance and Migration in the Godavari Estuarine Systems - Subramanyam, M (Fishery Technology, 1965)
Lunar, Diurnal and Tidal Periodicity in Relation to the Prawn Abundance and Migration in the Godavari Estuarine Systems